Outcomes of thin versus thick-wire snares for cold snare polypectomy: a systematic review and meta-analysis - Suprabhat Giri; Vaneet Jearth; Harish Darak; Sridhar Sundaram (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Cold snare polypectomy (CSP) is commonly used for the resection of colorectal polyps ≤10 mm. Data regarding the influence of snare type on CSP effectiveness are conflicting. Hence, this meta-analysis aimed to compare the outcomes and safety of thin- and thick-wire snares for CSP. Methods A comprehensive search of the literature published between 2000 and 2021 was performed of various databases for comparative studies evaluating the outcomes of thin- versus thick-wire snares for CSP. Results Five studies with data on 1,425 polyps were included in the analysis. The thick-wire snare was comparable to the thin-wire snare with respect to complete histological resection (risk ratio [RR], 1.03; 95% confidence interval [CI], 0.97-1.09), overall bleeding (RR, 0.98; 95% CI, 0.40-2.40), polyp retrieval (RR, 1.01; 95% CI, 0.97-1.04), and involvement of submucosa in the resection specimen (RR, 1.28; 95% CI, 0.72-2.28). There was no publication bias and a small study effect, and the relative effects remained the same in the sensitivity analysis. Conclusions CSP using a thin-wire snare has no additional benefit over thick-wire snares in small colorectal polyps. Factors other than snare design may play a role in improving CSP outcomes.